The Legal Status of Sustainable Development - Nasia Dikigoropoulou (2016)
Despite the widespread endorsement and political appeal of sustainable development, its seemingly ambiguous and vague nature has raised considerable controversy as its normative content and legal implications. That sustainable development was to have normative significance was evident since its introduction on the international political agenda by the 1987 World Commission on Environment and Development. The declaratory instruments which were subsequently adopted, and particularly the 1992 Rio Declaration and Agenda 21, have emphasized the need for the progressive development of international law on sustainable development. Despite developments, however, over the past 30 years and the widespread political endorsement of sustainable development by the international community, the legal status of sustainable development remains the subject of debate. Indeed there is little evidence to support a claim that there exists a legal obligation for states to develop sustainably. Nonetheless, it is proposed that, although international law may not strictly require development to be sustainable; there is a procedural obligation on states to adopt the appropriate state conduct and governance processes to strive to make progress towards sustainable development. The treaties and soft law documents which have endorsed sustainable development require states to adopt the necessary means to promote, ensure, contribute to, or work towards the fulfillment of the sustainable development objective. In this respect, its normativity lies not in requiring that a specific end result be fulfilled, but in requiring the adoption of all possible and available means necessary to strive to achieve that result. Its core principles of integration, ecological sustainability and public participation, provide for an identifiable list of measures which may be expected to be implemented by states as part of their efforts to facilitate progress to sustainable development, and against which state conduct may be assessed. Specific tools have been developed to facilitating the implementation of this obligation. The most notable of these is the environmental assessment regime. The environmental assessment process has been interpreted by the European Court of Justice as an instrument for sustainable development in light of its core principles. National case law in Cyprus also indicates that the national court has interpreted the law on environmental impact assessment in a way which recognizes such an obligation.